Professional Competence Of Educators In Islamic Boarding Schools: Training And Supervision - Hasan, Masykur; Patimah, Siti; Rinaldi, Achi (Journal of Advanced Islamic Educational Management, 2023)
Education in boarding schools has a significant role in character-building and increasing religious knowledge among students. However, to ensure that the education provided is by the times and the required competency standards, it is important to pay attention to the role of training and supervision in improving the professional competence of educators in boarding schools. This study aims to determine the effect of training and supervision on improving the professional competence of educators at Pondok Modern Darussalam Gontor Campus 7 Kalianda South Lampung. The method used in this research is to use a quantitative approach with an associative research type design. The sampling technique in this study used a probability sampling system. Data collection methods in this study include questionnaires/surveys, interviews, observation, and document analysis. The results stated that there was an influence of training on the professional competence of teachers at Pondok Modern Darussalam Gontor Campus 7. The positive influence given by training on teacher professional competence is 66.8% and the rest is influenced by other variables that are not studied. There is an influence of supervision on the professional competence of teachers at Pondok Modern Darussalam Gontor Campus 7 with a positive influence given by supervision on the professional competence of teachers at 61.9% and the rest is influenced by other variables not studied.